Evidence of small‐fiber neuropathy in neurofibromatosis type 1. Issue 6 (12th September 2019) - Barnett, Carolina; Alon, Tayir; Abraham, Alon; Kim, Raymond H.; McCuaig, Jeanna M.; Kongkham, Paul; Maurice, Catherine; Suppiah, Suganth; Zadeh, Gelareh; Bril, Vera
Abstract: Introduction: Large‐fiber neuropathy is rare in neurofibromatosis type 1, but small‐fiber neuropathy has not been studied. Methods: Patients with neurofibromatosis type 1 underwent nerve conduction studies for large‐fiber assessment. Small‐fiber tests included quantitative thermal thresholds, laser Doppler flare imaging, intraepidermal nerve fiber density, and corneal nerve fiber length. Results: Of the 52 patients enrolled, 31 (60%) were female and the mean age was 33.0 ± 12.3 years. Four (8%) patients had abnormal nerve conduction studies. Small‐fiber tests were frequently abnormal: thermal thresholds in 7 (13%); laser Doppler flare imaging in 10 (19%); intraepidermal nerve fiber density in 11 (22%); and corneal nerve fiber length in 27 (52%). The mean corneal nerve fiber length was below normative level (10.1 ± 2.7 mm/mm 3 ). Discussion: Small‐fiber neuropathy may be common in neurofibromatosis type 1, and should be investigated in symptomatic patients.